2001
DOI: 10.1348/026151001166173
|View full text |Cite
|
Sign up to set email alerts
|

Thematic and taxonomic relations in preschoolers: The development of flexibility in categorization choices

Abstract: International audienceTwo experiments examined the development of flexibility of categorization in children aged from 3 to 5, using a picture-matching task. During a pre-test, spontaneous matches were observed. Children were next presented with a scene aimed at inducing an alternative match. Finally, they were given a post-test identical to the pre-test to assess whether they would maintain their initial choice. Both experiments showed that preschoolers were able to produce different types of categorization ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
12

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 27 publications
5
59
0
12
Order By: Relevance
“…Thematic answers had to convey legitimate, salient schemata (e.g., "Apples grow on trees" and "Needles pull thread") but not ad hoc or perceptual relations (e.g., "Apples and trees are both found outside" and "Needles and thread are both tiny"). This scoring procedure is consistent with that of Blaye and Bonthoux (2001). Point-to-point interrater agreement on response accuracy was 98%.…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…Thematic answers had to convey legitimate, salient schemata (e.g., "Apples grow on trees" and "Needles pull thread") but not ad hoc or perceptual relations (e.g., "Apples and trees are both found outside" and "Needles and thread are both tiny"). This scoring procedure is consistent with that of Blaye and Bonthoux (2001). Point-to-point interrater agreement on response accuracy was 98%.…”
Section: Methodssupporting
confidence: 66%
“…Preschoolers demonstrate flexible categorization strategies, switching from thematic to taxonomic categories when context mandates (Blaye & Bonthoux, 2001;Nguyen & Murphy, 2003). In forced-choice matching tasks that include novel noun labels (e.g., this is a dax, find another dax), preschoolers tend to choose taxonomically rather than thematically (Waxman & Gelman, 1986).…”
mentioning
confidence: 99%
“…The flexible use of symbols including pictures has been argued to set humans apart from other species (DeLoache, 2004), and flexibility has been shown before in young children in categorization tasks (Blaye & Bonthoux, 2001;Defeyter, Avons, & German, 2007). Specifically, Defeyter et al (2007) found that 5-year-old children were able to generate more novel functions for familiar artifacts (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…psychologique, 2006, 106, 375-396 Relations entre objets Nos choix relatifs aux associations entre objets ont été déterminés par plusieurs considérations théoriques et par des objectifs de recherche fondamentale. La sélection des items a pris appui sur les études réalisées antérieurement chez les jeunes enfants (par exemple Baldwin, 1992;Blaye, Bernard-Peyron, & Bonthoux, 2000;Blaye & Bonthoux, 2001;Golinkoff, Shuff-Bailey, Olgin, & Ruan, 1995;Imai, Gentner, & Uchida, 1994;Lucariello, Kyratzis, & Nelson, 1992;Markman & Hutchinson, 1984;Rosch, Mervis, Gray, Johnson, & Boyes-Braem, 1976;Sell, 1992;Smiley & Brown, 1979;Waxman & Namy, 1997). Une liste des catégories les plus souvent utilisées a d'abord été établie.…”
Section: Objets Isolésunclassified
“…L'objectif est de remédier à l'absence de telles normes en langue française afin de fournir un outil méthodologique rigoureux aux chercheurs, évitant ainsi les multiples tests préalables à la constitution des protocoles expérimentaux utilisant du matériel imagé (voir par exemple Blaye & Bonthoux, 2001;Scheuner, Bonthoux, Cannard, & Blaye, 2004;Waxman & Namy, 1997). Ces normes sont accessibles sur le Web et concernent 274 images d'objets dessinés au trait, dont 150 images de Snodgrass et Vanderwart (1980), l'ensemble d'images le plus utilisé dans le monde.…”
Section: Introductionunclassified